PENERAPAN METODE THINK TALK WRITE DALAM PEMBELAJARAN MENULIS TEKS IKLAN PADA SISWA MTs MOHAMAD TOHA CIMAHI - sri, sri irawati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is motivated by the low interest of students in learning Indonesian subjects, because for those in Indonesian subjects some of the material requires them to be clever in expressing ideas or ideas, especially in writing ad text. Researchers use the think talk write method to motivate students, help develop ideas and imagination in writing ad text. The Think Talk Write method is a learning method that pumps students' motivation in developing their own business skills. This study aims to determine the differences in the ability and implementation of learning students who are given the application of the Discovery Learning treatment model in the control class and students who applied the think talk write treatment method in the experimental class. In this study the method used is the Quasi Experimental Design used is the pretest-postest Control Group Design. The objects that were sampled in this study were 30th grade VIII-A students, and 30th grade VIII-B students. Based on the results of the study, it can be concluded that the think talk write method is better than the Discovery Learning model. When students are treated with the think talk write method the value obtained is very good, can be seen from the posttest results the average student gets a score of 76.70, compared to when students are treated (treatment) using the average Discovery Learning model the students only get a score of 56.50.